A UNIFORM CATALOG OF MOLECULAR CLOUDS IN THE MILKY WAY - Rice, Thomas S.; Goodman, Alyssa A.; Bergin, Edwin A.; Beaumont, Christopher; Dame, T. M. (The Astrophysical journal, 2016)
ABSTRACT The all-Galaxy CO survey of Dame et al. is by far the most uniform, large-scale Galactic CO survey. Using a dendrogram-based decomposition of this survey, we present a catalog of 1064 massive molecular clouds throughout the Galactic plane. This catalog contains 2.5 × 108 solar masses, or 25 − 5.8 + 10.7 % of the Milky Way's estimated H2 mass. We track clouds in some spiral arms through multiple quadrants. The power index of Larson's first law, the size-linewidth relation, is consistent with 0.5 in all regions-possibly due to an observational bias-but clouds in the inner Galaxy systematically have significantly (∼30%) higher linewidths at a given size, indicating that their linewidths are set in part by the Galactic environment. The mass functions of clouds in the inner Galaxy versus the outer Galaxy are both qualitatively and quantitatively distinct. The inner Galaxy mass spectrum is best described by a truncated power law with a power index of γ = −1.6 0.1 and an upper truncation mass of M0 = (1.0 0.2) × 107 M , while the outer Galaxy mass spectrum is better described by a non-truncating power law with γ = −2.2 0.1 and an upper mass of M0 = (1.5 0.5) × 106 M , indicating that the inner Galaxy is able to form and host substantially more massive GMCs than the outer Galaxy. Additionally, we have simulated how the Milky Way would appear in CO from extragalactic perspectives, for comparison with CO maps of other galaxies.